Economic and legal aspects of labor market regulations in the modern Kazakhstan - Maidyrova, Aigul; Mamedova Aibeniz Tariverdi кizi (Business: Theory and Practice, 2013)
This article is devoted to study of the economic and legal aspects of the labor market regulations in the modern Kazakhstan. The article discloses the advantages of the state policy in the area of the economic and legal aspects of the labor market regulations, population employment and development of the practical recommendations in regards to improvement of the legal regulations mechanism. Directions of improvement of the legislative regulations of the labor market and the mechanism of the population employment regulations are proposed. The article also represents the methods of assessment of the population employment level as the indicator of the living standards.